The diagnostic and prognostic value of right ventricle systolic and diastolic function in inferior myocardial infarction patients - Purwaningtyas, Niniek (Global Health Management Journal, 2018)
Background: Inferior myocardial infarction (MI) with right ventricular (RV) involvement will increase mortality and morbidity. Data of systolic and diastolic RV function in inferior ST-segment elevation MI (STEMI) are useful to predict the RV involvement.  Aims: To evaluate the prognostic and diagnostic significance of RV systolic and diastolic function compared to RVMI diagnostic criteria by electrocardiography in inferior MI patients.Methods: Consecutive patients with first, acute, inferior STEMI were prospectively assessed. The RVMI was defined as an ST-segment elevation ≥ 0.1 mV in lead V4R. Echocardiography was performed within 24 hours of the inferior STEMI symptoms. We assessed the RVMI diagnostic criteria in inferior MI patients using echocardiography.Results: Out of 31 patients (mean age 56.39 ± 9.02 years), RVMI by electrocardiography and echocardiography was found in 18 (37%). Moreover, multivariate analysis showed that two variables — RV systolic and diastolic function, were independent predictors of RVMI in inferior MI patients. Sensitivity and specificity of the RV systolic function were 94.4% and 69.2%, respectively, while RV diastolic functions were 44% and 76.9%, respectively.Conclusion: RV systolic function predict RVMI with relatively high sensitivity and specificity. RV diastolic function predicts RVMI with relatively low sensitivity but with high specificity.